2016
DOI: 10.1175/jamc-d-16-0041.1
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Trend of Pan Evaporation over the Semiarid Loess Plateau under a Warming Climate

Abstract: In most parts of the world, pan evaporation decreases with increased air temperature rather than increases, which is known as the “evaporation paradox.” The semiarid Loess Plateau, which is sensitive to global climate change and ecological variations, has a unique warming and drying climate. The authors of this study consider whether pan evaporation shows the same decreasing trend in this unique environment. Meteorological observations of the typical semiarid Dingxi in the Loess Plateau from 1960 to 2010 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 30 publications
2
12
0
Order By: Relevance
“…The same phenomenon has been found in many parts of India, Australia, and China [19][20][21]. Some scholars have also found that the phenomenon of the evaporation paradox is obviously regional and seasonal, which makes the research on the trend of evapotranspiration continue to increase [22][23][24].…”
Section: Introductionsupporting
confidence: 58%
“…The same phenomenon has been found in many parts of India, Australia, and China [19][20][21]. Some scholars have also found that the phenomenon of the evaporation paradox is obviously regional and seasonal, which makes the research on the trend of evapotranspiration continue to increase [22][23][24].…”
Section: Introductionsupporting
confidence: 58%
“…2021, 11, 8013 2 of 14 trends in ET 0 in the Yellow River and the reduction of wind speed was the major driving force for decreasing trends. However, in recent years, increased ET 0 has been found in some regions, such as India and China [19]. Investigating long term change in ET 0 over India's humid tropical Narmada River watershed, Pandey et al [20] found an increasing trend in ET 0 .…”
Section: Introductionmentioning
confidence: 99%
“…The decrease in pan evaporation associated with the increasing air temperatures is called the "Pan Evaporation Paradox" [29]. Studies conducted in semi-arid regions point out that the combined contribution of cloud cover and relative humidity on pan evaporation is greater than that of temperature [30]. Thus, increased cloud cover offsets the increased pan evaporation because of temperature increase and relative humidity decrease.…”
Section: Discussionmentioning
confidence: 99%